Effect of V3+ Doping on the Structure and Electrochemical Properties of Na3MnTi(PO4)3 Cathode Material. Issue 1 (1st October 2022) - Lu, Lu; Hu, Pu; Xia, Yan; Tang, Ao
Abstract : The polyanionic compound Na3 MnTi(PO4 )3 with the NASICON framework has gotten a lot of attention as a cathode material for Na + cells. The stable structure of Na3 MnTi(PO4 )3 can bring good cycling stability, but it has a low theoretical specific capacity and bad rate capability, which hinders the practical application of the material. In this paper, the sol-gel technique with high-temperature annealing was used to make Na3 MnTi(PO4 )3 and Na3.7 MnTi0.3 V0.7 (PO4 )3 . It investigates how V 3+ doping affected the structure and electrochemical characteristics of the Na3 MnTi(PO4 )3 cathode material. The result displays that the Na3 MnTi(PO4 )3 and Na3.7 MnTi0.3 V0.7 (PO4 )3 synthesized phases are pure phases. The electrochemical performance result shows that a high discharge-specific capacity of 50.47 mAh/g may still be attained at 5 C. The discharge-specific capacity of Na3.7 MnTi0.3 V0.7 (PO4 )3 is still as great as 86.59 mAh/g after 100 cycles at 0.5 C. At 2 C, Na3.7 MnTi0.3 V0.7 (PO4 )3 has an ultra-high discharge specific capacity of 90.64 mAh/g and outstanding capacity retention of 84.77% after 300 cycles. The sample of Na3.7 MnTi0.3 V0.7 (PO4 )3 exhibits outstanding cycling performance and rate capability.